2012
DOI: 10.1089/lap.2011.0391
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cosmetic Outcome Between Single-Incision Laparoscopic Cholecystectomy and Conventional Laparoscopic Cholecystectomy: An Objective Study

Abstract: Patient perception regarding cosmetic outcome after SILC and CLC was similar in both groups. SILC does not seem to offer any significant cosmetic advantage over CLC. This point needs to be assessed in detail by larger studies, as cosmetic benefit is projected as one of the major advantages of single-incision surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 16 publications
(17 reference statements)
0
8
0
1
Order By: Relevance
“…Lirici et al not only demonstrated that SILC was associated with less postoperative pain, but also demonstrated superior patient satisfaction with SF36 in SILC patients compared to CLC patients [10]. However, some authors argued that CLC provided sufficient patient aesthetic satisfaction [11,12], with insignificant differences between the two groups [13].…”
Section: Discussionmentioning
confidence: 99%
“…Lirici et al not only demonstrated that SILC was associated with less postoperative pain, but also demonstrated superior patient satisfaction with SF36 in SILC patients compared to CLC patients [10]. However, some authors argued that CLC provided sufficient patient aesthetic satisfaction [11,12], with insignificant differences between the two groups [13].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed high level of satisfaction in SILC group. However, Ma et al [17] and Garg et al [18] reported that patients' perceptions regarding cosmetic outcome after SILC and CLC were similar in both groups. Hey et al [19] reported that patients ranked the level of risk for complications and postoperative pain above cosmetic results in determining their choice of procedure, if sufficient contemporary data of SILC is provided to patients.…”
Section: Discussionmentioning
confidence: 99%
“…[3] In a retrospective study from North India to compare SILS cholecystectomy and conventional laparoscopic cholecystectomy, Garg et al . [2] found similar overall satisfaction rates among the patients with the procedureof these two groups. In another retrospective study conducted in United Kingdom, Monkhouse et al .…”
mentioning
confidence: 88%
“…I agree completely with the authors that single incision laparoscopic surgery (SILS) has to go a long way before it is accepted as a safe procedure. Moreover, claims of higher patient satisfaction rate following SILS, one of the main projected benefit of this procedure, have been recently questioned in two studies, one from India[2] and another from United Kingdom. [3] In a retrospective study from North India to compare SILS cholecystectomy and conventional laparoscopic cholecystectomy, Garg et al .…”
mentioning
confidence: 99%